Establishment and comprehensive analysis of a new human cell line (NK-NJ) with NK-cell characteristics established from extranodal natural killer cell lymphoma/leukemia - Jin-Hua Liang; Wei-Ting Wang; Kai-Xin Du; Tong-Yao Xing; Yan Wang; Hui Wang; Lu Liu; Rui Guo; Yang Shao; Junheng Liang; Yue Li; Hao-Rui Shen; et al. (Human Cell, 2022)

Variations in trade-off of carbon storage and growth in subalpine larch across an elevational gradient - Rui He; Quan Zhou; Hang Shi; Haikun Liu; Wenting Zhu; Dongyue Yu; Quanfa Zhang; Haishan Dang (Trees, 2022)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Changes in the gut microbiota of osteoporosis patients based on 16S rRNA gene sequencing: a systematic review and meta-analysis - Rui Huang; Pan Liu; Yiguang Bai; Jieqiong Huang; Rui Pan; Huihua Li; Yeping Su; Quan Zhou; Ruixin Ma; Shaohui Zong; Gaofeng Zeng (Journal of Zhejiang University-SCIENCE B, 2022)

Pricing method and empirical study of China’s sea area resources assets - Tao Wang; Lu Yang; Rui Zhao; Stephen Hynes; Yue Yin; Cunji Liu; Yan Zheng; Lijing Deng (Journal of Coastal Conservation, 2022)

GITRL impairs the immunosuppressive function of MDSCs via PTEN-mediated signaling pathway in experimental Sjögren syndrome - Jie Tian; Beibei Zhang; Qingfang Yuan; Xueqing Sun; Na Peng; Bo Zhu; Chang Liu; Xiaoran Wang; Man Han; Meng Cao; Fan Xiao; Shengjun Wang; et al. (Inflammation Research, 2022)

Site-directed RNA editing by harnessing ADARs: advances and challenges - Ming Li; Cheng Yan; Yue Jiao; Yuqin Xu; Chen Bai; Rui Miao; Jiying Jiang; Jiao Liu (Functional & Integrative Genomics, 2022)

Effects and mechanism of ultrasound treatment on Chironomus kiiensis eggs - Bo-dong Liu; Hao-tao Dong; Hong-wei Rong; Rui-jian Zhang (Environmental Science and Pollution Research, 2022)

Spatial heterogeneity of greenhouse gas emissions from cereal crop production in China - Minghao Zhuang; Dario Caro; Wei Qin; Chun Wang; Xiaolin Yang; Rui Liu; Lin Zhang (Environmental Chemistry Letters, 2022)

Baicalin-berberine complex nanocrystals orally promote the co-absorption of two components - Ziwei Li; Yiting Liu; Jilin Wang; Xiaojiao Feng; Ebuka-Olisaemeka Nwafor; Ying Zhang; Rui Liu; Wenli Dang; Qingqing Zhang; Changxiang Yu; Jiaxin Pi; Zhidong Liu (Drug Delivery and Translational Research, 2022)

Agricultural Applications and Potential Risks of Copper-Based Nanoagrochemicals in Crop Cultivation - Yanwanjing Liu; Weichen Zhao; Yongguang Yin; Muhammad Adeel; Noman Shakoor; Yuanbo Li; Zhiqiang Tan; Yukui Rui; Qinghua Zhang; Jingfu Liu; Baoshan Xing (Reviews of Environmental Contamination and Toxicology, 2022)

Conodont Biostratigraphic Constraint on the Lower Taiyuan Formation in Southern North China and Its Paleogeographic Implications - Yuan Wang; Jianghai Yang; Dong-Xun Yuan; Jia Liu; Rui Ma (Journal of Earth Science, 2022)

Effects of coexposure to noise and mixture of toluene, ethylbenzene, xylene, and styrene (TEXS) on hearing loss in petrochemical workers of southern China - Yan Zhang; Yan Liu; Zongxin Li; Xin Liu; Qingfei Chen; Jingyao Qin; Qilong Liao; Rui Du; Qifei Deng; Yongmei Xiao; Xiumei Xing (Environmental Science and Pollution Research, 2022)

Environmental and economic benefits of substituting chemical potassium fertilizer with crop straw residues in China - Junhui Yin; Dongjia Li; Jingyao Yu; Xin Bai; Wenjing Cui; Rui Liu; Minghao Zhuang (Environmental Science and Pollution Research, 2022)

Synthesis of graphene oxide grafted by diazanyl groups and its application in recovery of lead from lead-acid wastewater - Chao-Zhi Zhang; Rui-Hua Jin; Qian-Qian Shen; Ling-Ling Liu (Environmental Science and Pollution Research, 2022)

Typhoon-Resistant Performance Assessment of Coastal Rural Residential Keel Brick Walls Reinforced with High Ductility Concrete - Qiang Li; Jun Zhang; Rui Wang; Jing Liu; Ping Li (Journal of Marine Science and Engineering, 2022)
The keel brick wall belongs to the rural residential exterior wall unique to the southeast coastal region of China. The wooden keel inside the wall and the external tie members can improve the stability of the whole wall. However, due to the age of construction, the wooden keel inside the existing residential keel brick walls has basically rotted and lost the tie with the external members, which seriously reduces the stability of the whole wall. Moreover, the collapse of keel brick walls caused by typhoons has become more and more frequent in recent years, seriously endangering the lives and properties of residents. Therefore, it is necessary to carry out reinforcement and repair for the existing residential buildings with keel brick walls. In this paper, the keel brick walls of rural houses in Ningbo area were taken as the research object, a framework for evaluating the performance of keel brick walls against typhoons was established, tests on the lateral force resistance of keel brick walls reinforced with high ductility concrete and mortar were carried out. With the help of typhoon full-track simulation and wind field simulation technology, the 600-year near-surface typhoon wind speeds affecting Ningbo area were obtained. A joint probability distribution model of multi-directional extreme wind speed was constructed using t-Copula function to determine the mixed wind climate of Ningbo area. The extreme wind loads that keel brick walls can withstand under four types of reinforcement were finally given. The results show that the high ductility concrete reinforcement has great advantages over mortar reinforcement and avoids brittle damage of the masonry structure. The keel brick walls reinforced with single-sided mortar can withstand wind loads of a 3-year return period, the keel brick walls reinforced with single-sided high ductile concrete can withstand extreme wind loads of a 110-year return period, while the keel brick walls reinforced with double-sided mortar as well as double-sided high ductile concrete can withstand extreme wind loads of well over a 110-year return period.

Analysis of Cyclic Shear Stress–Displacement Mechanical Properties of Silt–Steel Interface in the Yellow River Delta - Peng Yu; Jie Dong; Haisong Liu; Rui Xu; Rujie Wang; Meijun Xu; Hongjun Liu (Journal of Marine Science and Engineering, 2022)
Pile foundations of offshore structures are often subjected to cyclic loads under storm loads, thus reducing their vertical bearing capacity. Therefore, studying the cyclic shear behavior of the soil–structure interface is important for maintaining the stability of offshore structures. A series of cyclic shear tests of the silt–steel interface were carried out using a large interface shear apparatus. The effects of various factors (i.e., normal stress, shear displacement amplitude, roughness, and water content) on the shear stress characteristics of the silt–steel interface were investigated. The stress–displacement model of the cyclic shear silt–steel interface was deduced. The results showed that the shear stress at the silt–steel interface was softened, and the type of bulk deformation was shear shrinkage under cyclic shear. With the increase in shear amplitude, the hysteresis curve gradually developed from “parallelogram” to “shuttle” and “hysteresis cake”. With the increase in normal stress and roughness and the decrease in water content, the interfacial shear strength, volume displacements growth rate, and growth rate increased. The stress–displacement mathematical model of the silt–steel interface based on the modified hyperbolic model was in good agreement with the test data.

Birth-site habitat selection of wild alpine musk deer (Moschus chrysogaster) in the northeastern qing-tibetan plateau of China - Liquan Shen; Haoxiang Gao; Jiayi Wu; Gong Wang; Rui Liu; Jun Qi; Xueyan Zhang; Aiping Zhang; Lei Chen; Yizhen Zhang; Chunling Wang; Dongming Qi; et al. (Biologia, 2022)

Characteristics of water vapor sources and precipitation contributions to drought and wet events on the Chinese Loess Plateau - Rong Liu; Xin Wang; Zuoliang Wang; Rui Quan (Theoretical and Applied Climatology, 2022)

Modification of alternative splicing in bovine somatic cell nuclear transfer embryos using engineered CRISPR-Cas13d - Rui Cheng; Xiaoman Zheng; Yingmei Wang; Xing Ma; Xin Liu; Wenjun Xu; Mengyun Wang; Yuanpeng Gao; Xupeng Xing; Chuan Zhou; Hongzheng Sun; Zekun Guo; et al. (Science China Life Sciences, 2022)

MCPIP1 alleviated alcohol-induced immune dysfunction via the MAPK/ERK signaling pathway - Yanjie Shen; Kai Zhang; Rui Wang; Shuaichen Sun; Yating Yang; Yitan Yao; Huanzhong Liu; Zhenhua Ren (Psychopharmacology, 2022)

Tectonic framework of Eastern Tianshan in the Early Carboniferous: constraints from alkalic intrusive rocks - Yi-Hao Liu; Chun-Ji Xue; Yun Zhao; Rui Wang; Liang Yu (International Journal of Earth Sciences, 2022)

Novel and sustainable carboxylation of terminal alkynes and CO2 to alkynyl carboxylic acids using triazolium ionic liquid-modified PMO-supported transition metal acetylacetonate as effective cooperative catalysts - Jing-Rui Li; Chen Chen; Xiao-Bing Liu; Yu-Lin Hu (Environmental Science and Pollution Research, 2022)

What is the short-term outlook for the EU’s natural gas demand? Individual differences and general trends based on monthly forecasts - Nu Li; Jianliang Wang; Rui Liu; Yan Zhong (Environmental Science and Pollution Research, 2022)

The inhibition of CFTR in the descended testis of SD rats with unilateral cryptorchidism induced by di-(2-ethylhexyl) phthalate (DEHP) - Xiangliang Tang; Dian Li; Tianxin Zhao; Shibo Zhu; Xiaofeng Gao; Rui Zhou; Fuming Deng; Wen Fu; Wei Jia; Guochang Liu (Environmental Science and Pollution Research, 2022)

Associations of exposure to lead and cadmium with risk of all-cause and cardiovascular disease mortality among patients with type 2 diabetes - Kai Zhu; Yuge Zhang; Qi Lu; Tingting Geng; Rui Li; Zhenzhen Wan; Xuena Zhang; Yujie Liu; Lin Li; Zixin Qiu; Meian He; Liegang Liu; et al. (Environmental Science and Pollution Research, 2022)

Characterization of a Hyaluronidase-Producing Bacillus sp. CQMU-D Isolated from Soil - Lu Wang; Qianqian Liu; Rui Hao; Jing Xiong; Junxing Li; Yanan Guo; Lu He; Zeng Tu (Current Microbiology, 2022)

Genistein Alleviates Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus by Activating the Sirt1/Nrf2 Pathway in High Salt-Induced Hypertension - Li-Gang Niu; Na Sun; Kai-Li Liu; Qing Su; Jie Qi; Li-Yan Fu; Guo-Rui Xin; Yu-Ming Kang (Cardiovascular Toxicology, 2022)

Risk Assessment and Source Identification of Arsenic in Surface Sediments from Caohai Lake, China - Ying Tang; Xinmin Liu; Rui Tian; Rui Li; Hang Li (Bulletin of Environmental Contamination and Toxicology, 2022)

Characterization of thermal conductivity of seasonally frozen turfy soil from Northeastern China - Yuanyuan He; Yan Xu; Yan Lv; Lei Nie; Xiaoting Feng; Tingting Liu; Tao Zhang; Yuzheng Wang; Chao Du; Xiangjian Rui; Fansheng Kong (Bulletin of Engineering Geology and the Environment, 2022)

Continental‐scale niche differentiation of dominant topsoil archaea in drylands - Weigang Hu; Qingqing Hou; Manuel Delgado‐Baquerizo; James C. Stegen; Qiajun Du; Longwei Dong; Mingfei Ji; Yuan Sun; Shuran Yao; Haiyang Gong; Junlan Xiong; Rui Xia; et al. (Environmental Microbiology, 2022)
Archaea represent a diverse group of microorganisms often associated with extreme environments. However, an integrated understanding of biogeographical patterns of the specialist Haloarchaea and the potential generalist ammonia‐oxidizing archaea (AOA) across large‐scale environmental gradients remains limited. We hypothesize that niche differentiation determines their distinct distributions along environmental gradients. To test the hypothesis, we use a continental‐scale research network including 173 dryland sites across northern China. Our results demonstrate that Haloarchaea and AOA dominate topsoil archaeal communities. As hypothesized, Haloarchaea and AOA show strong niche differentiation associated with two ecosystem types mainly found in China's drylands (i.e. deserts vs. grasslands), and they differ in the degree of habitat specialization. The relative abundance and richness of Haloarchaea are higher in deserts due to specialization to relatively high soil salinity and extreme climates, while those of AOA are greater in grassland soils. Our results further indicate a divergence in ecological processes underlying the segregated distributions of Haloarchaea and AOA. Haloarchaea are governed primarily by environmental‐based processes while the more generalist AOA are assembled mostly via spatial‐based processes. Our findings add to existing knowledge of large‐scale biogeography of topsoil archaea, advancing our predictive understanding on changes in topsoil archaeal communities in a drier world.

Two new triterpenoid glycosides from leaves of Cyclocarya paliurus - Huihui Sun; Hui Zhu; Jianping Wu; Yuyan Wang; Guihua Li; Yiqian Liu; Xiwen Chang; Saiyu Ou; Wenwen Zha; Huiyun Chen; Rui Gui; Xiaoai He; et al. (Natural Product Research, 2022)

Monoterpenoid indole alkaloids with potential neuroprotective activities from the stems and leaves of Melodinus cochinchinensis - Yu-Jie Li; Juan Li; Lan Xie; Jun-Yu Zhou; Qiu-Xuan Li; Rui-Yuan Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2022)

Exploring key sectors of CO2 emissions and driving factors to spatiotemporal evolution in China from multiple perspectives - Xianmei Liu; Rui Peng; Caiquan Bai; Song Wang (Environmental Science and Pollution Research, 2022)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

The Impact of Sugarcane Brown Rust and Host Resistance on the Phyllosphere Bacterial Community - Xiaoning Gao; Hui Sun; Rui Liu; Zilin Wu; Yongwen Qi (Sugar Tech, 2022)

SLAH1 is involved in the long-distance transport of Cl− from roots into shoots in the Cl−-tolerant xerophyte Pugionium cornutum under salt stress - Yan-Nong Cui; Xiao-Yu Li; Rui-Wen Liu; Zi-Hua He; Suo-Min Wang; Qing Ma (Plant and Soil, 2022)

Nutrient Reabsorption Mechanism Adapted to Low Phosphorus in Wild and Cultivated Soybean Varieties - Wenyue Shen; Rui Guo; Yaxuan Zhao; Danping Liu; Jing Chen; Ningning Miao; Shujuan Gao; Tao Zhang; Lianxuan Shi (Journal of Plant Growth Regulation, 2022)

Screening of microRNA and mRNA related to secondary hair follicle morphogenesis and development and functional analysis in cashmere goats - Fangzheng Shang; Yu Wang; Rong Ma; Youjun Rong; Min Wang; Zhihong Wu; Erhan Hai; Jianfeng Pan; Lili Liang; Zhiying Wang; Ruijun Wang; Rui Su; et al. (Functional & Integrative Genomics, 2022)
microRNA (miRNA) is a type of endogenous short-chain non-coding RNA with regulatory function found in eukaryotes, which is involved in the regulation of a variety of cellular and biological processes. However, the research on the development of cashmere goat secondary hair follicles is still relatively scarce. In this study, small RNA libraries and mRNA libraries of 45 days, 55 days, 65 days, and 75 days of fetal skin of cashmere goats were constructed, and the constructed libraries were sequenced using Illumina Hiseq4000, and the expression profiles of miRNA and mRNA in cashmere goat fetal skin were obtained. The differentially expressed miRNAs and mRNAs in six control groups were identified and the qRT-PCR experiment shows that the sequencing results are accurate. Sixty-six miRNAs related to secondary hair follicle development were screened, and used TargetScan and miRanda to predict 33 highly expressed miRNA target genes. At the same time, 664 mRNAs related to the development of secondary hair follicles were screened, and GO enrichment and KEGG pathway analysis were performed. It was found that some miRNA target genes were consistent with the screening results of mRNAs related to secondary hair follicle development and were enriched in Notch signaling pathway, TGF-β signaling pathway. Therefore, miR-145-5p-DLL4, miR-27b-3p-DLL4, miR-30e-5p-DLL4, miR-193b-3p-TGF-β1, miR-181b-5p-NOTCH2, and miR-103-3p-NOTCH2 regulatory network related to the development of secondary hair follicles were constructed and the results of dual-luciferase reporter gene assay indicated that there is a targeted relationship between chi-miR-30e-5p and DLL4, which will provide a basis for molecular mechanism of miRNA-mRNA in the development of the hair follicles in cashmere goats.

Effect of winter feeding frequency on growth performance, biochemical blood parameters, oxidative stress, and appetite-related genes in Takifugu rubripes - Xiaoqiang Gao; Xinyi Wang; Xi Wang; Hongxu Li; Liang Xu; Yingying Fang; Shuquan Cao; Bin Huang; Haibin Chen; Rui Xing; Baoliang Liu (Fish Physiology and Biochemistry, 2022)

Assessment of trace element contamination in the historical nesting grounds of green sea turtle (Chelonia mydas) in Hainan Island, China - Ting Zhang; Liu Lin; Deqin Li; Li Jian; Rui Li; Jichao Wang; Haitao Shi (Environmental Science and Pollution Research, 2022)

The cytotoxicity of PM2.5 and its effect on the secretome of normal human bronchial epithelial cells - Zhigang Sui; Xiaoyao Song; Yujie Wu; Rui Hou; Jianhui Liu; Baofeng Zhao; Zhen Liang; Jiping Chen; Lihua Zhang; Yukui Zhang (Environmental Science and Pollution Research, 2022)

Integration of ABC curve, three dimensions of alpha diversity indices, and spatial patterns of fish assemblages into the health assessment of the Chishui River basin, China - Fandong Yu; Fei Liu; Zhijun Xia; Chunsen Xu; Jianwei Wang; Rui Tang; Zujun Ai; Youzhao Zhang; Miaomiao Hou; Xinhua Zou (Environmental Science and Pollution Research, 2022)

Associations of urinary polycyclic aromatic hydrocarbon metabolites and blood pressure with the mediating role of cytokines: A panel study among children - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Jie Yu; Shuang Chen; Meng Li; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Environmental Science and Pollution Research, 2022)

Promotion effect of graphene on phytoremediation of Cd-contaminated soil - Xingyu Deng; Rui Liu; Liqun Hou (Environmental Science and Pollution Research, 2022)

Spatiotemporal variations of water quality and their driving forces in the Yangtze River Basin, China, from 2008 to 2020 based on multi-statistical analyses - Shasha Liu; Rui Fu; Yun Liu; Chengyu Suo (Environmental Science and Pollution Research, 2022)

Pharmaceutical nanoformulation strategies to spatiotemporally manipulate oxidative stress for improving cancer therapies — exemplified by polyunsaturated fatty acids and other ROS-modulating agents - Rui Xue Zhang; Franky Fuh-Ching Liu; Hoyin Lip; Junhong Liu; Qianrong Zhang; Xiao Yu Wu (Drug Delivery and Translational Research, 2022)

Compounding soils to improve cropland quality: A study based on field experiments and model simulations in the loess hilly-gully region, China - Yun-xin Huang; Zheng-jia Liu; Yan-sui Liu; Yu-rui Li; Xue-qi Liu (Journal of Mountain Science, 2022)

Direct Radiative Effects of Dust Aerosols over Northwest China Revealed by Satellite-Derived Aerosol Three-Dimensional Distribution - Rui Jia; Yuzhi Liu; Yan Li; Jun Li; Xiaolin Hu; Ronglu Gao; Yunfei Tian; Yanling Sun; Nannan Mu; Minfen Zhao (Journal of Meteorological Research, 2022)

Ionosphere-weighted post-processing kinematic for airborne positioning with refined modeling of receiver phase biases and tropospheric zenith wet delays - Rui Gao; Zhizhao Liu; Baocheng Zhang (GPS Solutions, 2022)

Meshless Surface Wind Speed Field Reconstruction Based on Machine Learning - Nian Liu; Zhongwei Yan; Xuan Tong; Jiang Jiang; Haochen Li; Jiangjiang Xia; Xiao Lou; Rui Ren; Yi Fang (Advances in Atmospheric Sciences, 2022)

Fosthiazate exposure induces oxidative stress, nerve damage, and reproductive disorders in nontarget nematodes - Shiling Liu; Qiqi Wu; Yanru Zhong; Zongzhe He; Zhen Wang; Rui Li; Minghua Wang (Environmental Science and Pollution Research, 2022)

Determination of the main alkaloids and their insecticidal activity of extract of Areca catechu nuts against Plutella xylostella - Rui Liu; Minyuan Zheng; Lin Yuan; Zhonglin Liu; Jianqiang Bao; Wenchao Yang; Hailong Kong; Jianguo Feng (International Journal of Tropical Insect Science, 2022)

Can green finance promote urban green development? Evidence from green finance reform and innovation pilot zone in China - Hongfeng Zhang; Yixiang Wang; Rui Li; Hongyun Si; Wei Liu (Environmental Science and Pollution Research, 2022)

Aluminum-activated Malate Transporter 12 is involved in restricting root-to-shoot Cl− transport in Arabidopsis under Cl−-salt stress - Rui-Wen Liu; Jian-Zhen Yuan; Xiao-Yu Li; Yan-Nong Cui; Mei-Mei Cai; Zi-Hua He; Qing Ma (Plant and Soil, 2022)

Genotypic variations in GST genes reveal a regulatory role in the accumulation of caffeoylquinic acids in leafy sweet potato (Ipomoea batatas) - Deka Reine Judesse Soviguidi; Yi Liu; Rui Pan; Salah Fatouh Abou-Elwafa; Wen-Ying Zhang; Xin-Sun Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Wnt Signaling Pathways: A Role in Pain Processing - Yiting Tang; Yupeng Chen; Rui Liu; Weidong Li; Baojin Hua; Yanju Bao (NeuroMolecular Medicine, 2022)
The wingless-related integration site (Wnt) signaling pathway plays an essential role in embryonic development and nervous system regulation. It is critically involved in multiple types of neuropathic pain (NP), such as HIV-related NP, cancer pain, diabetic neuralgia, multiple sclerosis-related NP, endometriosis pain, and other painful diseases. Wnt signaling is also implicated in the pain induced by sciatic nerve compression injury and selective spinal nerve ligation. Thus, the Wnt signaling pathway may be a potential therapeutic target for NP.

Orbit determination, clock estimation and performance evaluation of BDS-3 PPP-B2b service - Chengpan Tang; Xiaogong Hu; Jinping Chen; Li Liu; Shanshi Zhou; Rui Guo; Xiaojie Li; Feng He; Jinhuo Liu; Jianhua Yang (Journal of Geodesy, 2022)

Uncertainty health risk assessment and regional control of drinking water: a case study of Hanyuan County, southwest mountainous area, China - Zhengjiang Lin; Ying Liu; Zhihui Cheng; Rui Zhao; Han Zhang (Environmental Science and Pollution Research, 2022)

Machine Learning Tools for Fossil and Geothermal Energy Production and Carbon Geo-sequestration—a Step Towards Energy Digitization and Geoscientific Digitalization - Siddharth Misra; Rui Liu; Aditya Chakravarty; Keyla Gonzalez (Circular Economy and Sustainability, 2022)

Monitoring glaciers in the Chenab basin with SBAS InSAR technology - Yue-kai Ding; Rui Liu; Yi-fei Fan; Ling-xiang Zhou; Qin Ji; Hong Zhang; Zuo-lin Xiao (Journal of Mountain Science, 2022)

Impact of climate change on long-term variations of small yellow croaker (Larimichthys polyactis) winter fishing grounds - Rui Zhang; Yang Liu; Hao Tian; Shuhao Liu; Kaiwei Zu; Xinmei Xia (Frontiers in Marine Science, 2022)
Small yellow croaker ( Larimichthys polyactis ) is one of the key demersal species with high economic values and wide distribution in the China Seas. In this study, a Winter Fishing ground Abundance Index (WFAI) was developed by using fisheries survey data in 1971–1982 and used as the response variable to investigate the impacts of environmental variables, including surface current velocity (SCV), sea surface salinity (SSS), sea surface temperature (SST), and depth (DE). A total of 45 combinatorial generalized additive models (GAMs), generalized linear models (GLMs), and random forest models (RFs) were used to select the optimal WFAI prediction. The final WFAI distribution results showed that the winter fishing ground hotspots of small yellow croaker were mainly distributed between 11°C and 16°C isotherms and between 50-m and 100-m isobaths, and the area of winter fishing ground hotspots (WFHA) significantly decreased and the hotspots tended to move northward over the past 50 years. The shape of hotspots was strongly affected by temperature fronts and salinity fronts. Analysis with the climate indices revealed that the Atlantic Multidecadal Oscillation (AMO) might have a large influence on the distribution of small yellow croaker by affecting SST and SSS in the China Seas more than the Pacific Decadal Oscillation (PDO), North Pacific Gyre Oscillation (NPGO), and Arctic Oscillation Index (AOI). The future prediction based on two extreme scenarios (RCP2.6 and RCP8.5) indicated that the hotspots would obviously move northward. These findings will serve effectively the fishery resources monitoring, management, and evaluation of small yellow croaker in the China Seas.

Research on PEMS Test Data Processing Method and Cold Start Emission Evaluation Method of Heavy-Duty Diesel Vehicles - Gangzhi Tang; Shuaibin Wang; Rui Wang; Baocheng Du; Yu Liu; Gang Tian; Linyao Ran; Gan Xiang; Huang Li (Water, Air, & Soil Pollution, 2022)

Magnetic Resonance Imaging Markers of Cerebral Small Vessel Disease in Adults with Moyamoya Disease - Haogeng Sun; Wanjiang Li; Chao Xia; Yutao Ren; Lu Ma; Anqi Xiao; Chao You; Xiaoyu Wang; Rui Tian; Yi Liu (Translational Stroke Research, 2022)

Plant-mediated rhizospheric interactions in rice and water spinach intercropping enhance Si uptake by rice - Chuanchuan Ning; Lei Wang; Rui Liu; Taowen Pan; Yixia Cai; Jihui Tian; Shiming Luo; Kunzheng Cai (Plant and Soil, 2022)

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

High-Frequency Repetitive Transcranial Magnetic Stimulation Regulates Astrocyte Activation by Modulating the Endocannabinoid System in Parkinson’s Disease - Xin Kang; Bing Zhang; Wanqing Du; Rui Zhao; Xuedong Liu; Ya Bai; Xiaobing Jiang; Jie Pang; Chenguang Zhao; Xiang Mou; Fang Gao; Hua Yuan; et al. (Molecular Neurobiology, 2022)

RNAi-Based Transcriptome Suggests Candidate Genes Regulated by ZxNHX1 to Affect The Salt Tolerance of Zygophyllum xanthoxylum - Hai-Shuang Liu; Xiao-Nong Guo; Wei-Wei Chai; Rui-Xin Zhang; Pei-Qin Li; Cui-Min Ma; Qing Ma; Suo-Min Wang (Journal of Plant Growth Regulation, 2022)

A novel therapeutic strategy for atherosclerosis: autophagy-dependent cholesterol efflux - Haipeng Guo; Dongmei Wei; Rui Liu; Chao Zhang; Song Jiang; Weijia Wang; Hongzhe Hu; Lijuan Shen; Xiaofei Liang (Journal of Physiology and Biochemistry, 2022)

ACOT7 protects epidermal stem cells against lipid peroxidation - Guang Zhang; Jiaxu Ma; Zhenjie Wu; Guoqi Cao; Chunyan Liu; Ru Song; Rui Sun; Aoyu Chen; Yibing Wang; Siyuan Yin (In Vitro Cellular & Developmental Biology - Animal, 2022)
Epidermal stem cells (ESCs) are critical for skin regeneration and repair. Previous studies have shown that ESCs are susceptible to oxidative stress, which in turn leads to lipid peroxidation and affects skin repair. Our study aims to explore how ESCs resist lipid peroxidation. By performing proteomics analysis, we found that the expression of Acyl-CoA thioesterase 7 (ACOT7) was positively correlated with the concentration of transferrin. Overexpression adenovirus vectors of ACOT7 were constructed and transfected into ESCs. Levels of lipid peroxidation by flow cytometry, cell viabilities, and MDA levels were measured. The results revealed that ACOT7 could inhibit lipid peroxidation, reduce the level of malondialdehyde (MDA), and improve the survival rate of ESCs induced by H 2 O 2 , Erastin, and RSL3. Our data suggest that ACOT7 has an effect on protecting ESCs against iron-dependent lipid peroxidation.

Validation of reliable safe harbor locus for efficient porcine transgenesis - Xiang Ma; Weijun Zeng; Lei Wang; Rui Cheng; Zeying Zhao; Caiyun Huang; Zhongxin Sun; Peipei Tao; Tao Wang; Jufang Zhang; Lu Liu; Xing Duan; et al. (Functional & Integrative Genomics, 2022)

Hierarchical collagen fibers complexed with tannic acid and Fe3+ as a heterogeneous catalyst for enhancing sulfate radical-based advanced oxidation process - Rui Wang; Ruiquan Yu; Junchao Wang; Jun Xiang; Chaojian Chen; Gongyan Liu; Xuepin Liao (Environmental Science and Pollution Research, 2022)

Preparing porous Cu/Pd electrode on nickel foam using hydrogen bubbles dynamic template for high-efficiency and high-stability removal of nitrate from water - Jialu Shi; Ya Gao; Daoru Liu; Zhanhui Shen; Jing Fan; Yating Yu; Meihui Bao; Panpan Li; Rui Yao (Environmental Science and Pollution Research, 2022)

Influence of different inoculation densities of black soldier fly larvae (Hermetia illucens) on heavy metal immobilization in swine manure - Dongmei Jiang; Kunhong Jiang; Rui Li; Liangbin Zhao; Zile Liu; Bangjie Xiong; Du Jin; Xiaoxia Hao; Li Zhu; Bo Kang; Lin Bai (Environmental Science and Pollution Research, 2022)

Construction of a mutant Bacillus subtilis strain for high purity poly-γ-glutamic acid production - Linlin He; Lu Liu; Rui Ban (Biotechnology Letters, 2022)

Molecular Characterization, Expression Pattern and Transcriptional Regulation of Figla During Gonad Development in Japanese Founder (Paralichthys olivaceus) - Jiangbo Qu; Rui Li; Yuxiang Liu; Minmin Sun; Weijie Yan; Jinxiang Liu; Xubo Wang; Quanqi Zhang (Journal of Ocean University of China, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

The effects of dietary fermented wheat bran polysaccharides on mucosal and serum immune parameters, hepatopancreas antioxidant indicators, and immune-related gene expression of common carp (Cyprinus carpio) juveniles - Rui-Fang Wang; Yuan Wang; Jun Zhang; Mei-Qi Weng; Yu-Hui Liu; Qiu-Yan Cheng; Min Song; Yan-Ping Yang; Xiao-Ping An; Jing-Wei Qi (Aquaculture International, 2022)

Assessing trophic interactions among three tuna species in the Solomon Islands based on stomach contents and stable isotopes - Ri Jin Jiang; Fan Yang; Feng Chen; Rui Yin; Ming Zhi Liu; Wen Bin Zhu; Ai Guo; Lian Wei Liu (Frontiers in Marine Science, 2022)
Trophic research is essential to the conservation and management of fishery resources. This study analyzed the feeding habits and nutritional interactions among three tuna species in the waters of the Solomon Islands (5°12′S–15°20′S, 157°31′E–172°19′E). A total of 103 bigeye tuna ( Thunnus obesus ), 296 yellowfin tuna ( Thunnus albacores ), and 264 albacore tuna ( Thunnus alalunga ) samples were collected from September to December 2019. Samples for stomach content and stable isotope analysis were randomly selected. The stomach content analysis results showed that the stomach contents of the three tuna species were rich in prey, and 48 prey species were identified, including fish, cephalopods, and crustaceans, with high between-phenotype component (BPC). Yellowfin tuna consumed the largest variety of food and bigeye tuna consumed the smallest. The feeding intensity of bigeye tuna were higher than that of yellowfin and albacore tuna. Yellowfin tuna had the highest empty stomach rate (35.69%) and lowest average stomach fullness index (0.064). The degree of stomach fullness in the three tuna species was mainly 1, and the difference in the stomach fullness index among them was significant ( P <0.001). Food overlap (0.3–0.6) and Levins index (<0.6) among the three species were low, indicating a specialized feeding tendency. Bigeye tuna mainly feed on Ommastrephes bartrami and Myctophidae, yellowfin tuna mainly feed on Hyperiidea and Aluterus monoceros , and albacore tuna mainly feed on Gempylus serpens and Loligo chinensis . The stable isotope results showed that the δ 13 C and δ 15 N values of the three tuna species were significant ( P <0.001). The standard ellipse area corrected for small sample sizes (SEAc) and total niche area (TA) of bigeye tuna, range of δ 15 N (NR) of yellowfin tuna, and range of δ 13 C (CR) of albacore tuna were the highest. The results of this study will help improve our understanding of the feeding ecology of these three tuna species and their important roles in the ecosystem and food web structure.

Electrospun nanofibers food packaging: trends and applications in food systems - Dur E. Sameen; Saeed Ahmed; Rui Lu; Rui Li; Jianwu Dai; Wen Qin; Qing Zhang; Suqing Li; Yaowen Liu (Critical Reviews in Food Science and Nutrition, 2022)

Modeling, Control and Experiments of a Novel Underwater Vehicle with Dual Operating Modes for Oceanographic Observation - Junjun Cao; Rui Lin; Baoheng Yao; Chunhu Liu; Xiaochao Zhang; Lian Lian (Journal of Marine Science and Engineering, 2022)
Multifarious and continuous oceanographic observation data is of considerable significance to oceanographic research and military application. In this paper, a novel oceanographic observation method with dual-modal underwater vehicle able to switch between the Argo and Glider modes is proposed and is studied experimentally in the South China Sea. Using the Newton–Euler formulation, a complete dynamic model considering the variation in gravity/buoyancy due to mode switching is thus established. Then, based on Lyapunov stability criterion, a nonlinear adaptive inverse controller with multiple inputs and multiple outputs is developed which enables the observation platform to freely switch between various modes. By analyzing the numerical and experimental data of a single mode, the results demonstrate that the proposed method can supplement the observation data and improve the accuracy of oceanographic data. Finally, based on experimental data acquired by the dual-modal underwater vehicle in the South China Sea, three-dimensional regional oceanic temperature and salinity fields are constructed with the spatio-temporal Kriging method, and feature surfaces are extracted from the oceanic fields. Furthermore, the proposed method can be applied in other stirring dynamic regions, such as ocean eddies, ocean fronts, filaments, etc.

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Behavioral differentiation among workers may reduce reproductive conflicts during colony inheritance in the termite Reticulitermes labralis - Zhuangdong Bai; Yibin Liu; David Sillam-Dussès; Rui-Wu Wang (Insectes Sociaux, 2022)

Acetylsalicylic acid (ASA) suppressed Fusarium rot development and neosolaniol (NEO) accumulation by activating phenylpropane metabolism in muskmelon fruit - Lan Li; Qili Liu; Huali Xue; Yang Bi; Hussain Raza; Rui Zhang; Jimdjio Kouasseu Carelle; Hui Peng; Haitao Long; Dov Prusky (European Journal of Plant Pathology, 2022)

Simvastatin as an emerging pollutant on non-target aquatic invertebrates: effects on antioxidant-related genes in Daphnia magna - Sijia Liu; Jiawei Lin; Rui Ding; Xiangping Nie (Environmental Science and Pollution Research, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Selenomethionine Alleviates Intestinal Ischemia–Reperfusion Injury in Mice Through the Bax-Caspase Pathway - Zhe Liu; Guangze Mou; Zhiming Liang; Rui Zhao; Chenghao Jin; Rui Wu (Biological Trace Element Research, 2022)

Characteristics and changes of the Himalayas glacial area in China during 1990–2015 - Shu-xian Shi; Li Xing; Yue-kai Ding; Jun Dong; Rui Liu; Qin Ji; Zuo-lin Xiao; Xun Huang (Journal of Mountain Science, 2022)

A study on the infection status and transmission of avian leukosis virus subgroup J in Hy-line brown roosters - Fanfeng Meng; Qiuchen Li; Rui Han; Guanlong Xu; Xintao Gao; Fubing Luo; Guangnian Shen; Xiaodong Liu; Zhifang Zhang; Peng Zhao; Guozhong Zhang (Archives of Virology, 2022)

Full genome sequence of a novel iflavirus from the leafhopper Recilia dorsalis - Rui Ma; Binghua Nie; Jiajia Chen; Keliang Lv; Jiajing Xiao; Renyi Liu (Archives of Virology, 2022)

Phosphorus Absorption and Excretion in Hybrid Sturgeon (Huso dauricus♀ X Acipenser schrenckii♂) Intubated with Different Ca/P Ratios - Jiali Jin; Zhipeng Chu; Rui Ruan; Wei Liu; Xihua Chen; Chuangju Li (Fishes, 2022)
To study the effect of Ca/P ratio on the P and Ca absorption and excretion in hybrid sturgeon (Huso dauricus♀ X Acipenser schrenckii♂), five groups of fish were intubated with 100 mg P·kg−1 BW with the Ca/P ratios of 0:1, 0.25:1, 0.5:1, 1:1, and 2:1. Plasma P concentrations were significantly elevated at Ca/P ratios below 2:1, and the highest value was obtained at Ca/P ratio of 0.5:1. Plasma Ca content was significantly increased at the highest Ca/P ratio. Urine P excretion rate in the fish intubated with Ca/P ratio of 0.5:1 was significantly higher than that of the groups with Ca/P ratios of 0:1 and 2:1. The highest urea excretion rates were observed at Ca/P ratio of 0.5:1 and 1:1. The total P excretion at 48 h post intubation reached about 30 mg·kg−1 BW, which was recorded for the group with Ca/P ratio of 0.5:1. The present study showed that P absorption efficiency was improved in hybrid sturgeon at Ca/P ratio of 0.5:1, indicating that P inclusion level in sturgeon feed can be further optimized to reduce dietary P input and lower the excessive undigested P discharge into the rearing water.

Otolith Marking With Strontium for Stock Assessment in Coilia nasus - Ming-Zhi Liu; Ri-jin Jiang; Hui Zhang; Fan Yang; Xia-Fang Li; Guang-Peng Feng; Rui Yin; Feng Chen (Frontiers in Marine Science, 2022)
Mass stock enhancement and release are excellent ways to recover Coilia nasus resources. However, it is challenging to evaluate stock enhancement effectively, and it is important to establish a method suitable for estimating C. nasus populations. We explored the effectiveness of marking otoliths in these fish with strontium by immersing C. nasus in hexahydrate strontium chloride solutions. We used laser ablation inductively coupled plasma mass spectrometry to measure the strontium content of otoliths and fish bodies. The larvae (40 d post hatch) were reared in five different concentrations of strontium (0, 12, 24, 48, and 60 mg/L) for 7 d, followed by treatment in non-additive water for 3 wk. The results showed that the cumulative mortality rate was not significantly different between treatment and control groups ( P >0.05), except in the group treated with 24 mg/L strontium. The swimming and feeding behaviors did not change significantly, indicating that strontium did not negatively affect survival in this species. The strontium/calcium ratios of otoliths in the control group were stable (1.78–2.32 mmol/mol), whereas those of the experimental (marked) groups ranged widely (4.47–61.02 mmol/mol). The strontium/calcium ratios increased with increasing strontium concentration, but gradually returned to baseline values, resulting in a 100% success rate of marking with strontium. Following immersion in 12 mg/L strontium, strontium levels in the body returned to normal after 24 d. In summary, a treatment of 12 mg/L strontium for 4 d was identified as viable for marking. We confirmed the feasibility of strontium marking for the mass marking and release of C. nasus . This marking method does not affect the physiology of the fish and may provide a new approach for reasonable and scientific stock assessment of C. nasus post hatch.

Risk Evaluation of Navigation Environment Based on Dynamic Weight Model and Its Application - Shuzhe Chen; Lei Wu; Cheng Xie; Li Zhou; Rui Wang; Zhao Liu; Quanlong Zhu; Lianzhong Zhu (Journal of Marine Science and Engineering, 2022)
In order to scientifically and reasonably evaluate the safety risk of ship navigation, to and better solve the problems of the poor sensitivity of static evaluation and insufficient ability to grasp the overall dynamic situation, in this paper, representative safety evaluation indexes for ship navigation are screened and the initial weight of each index is confirmed in combination with the improved analytic hierarchy process (IAHP), in order to learn the changes of navigation environment and accident samples in the waters in the jurisdiction. Finally, the dynamic risk evaluation is carried out by constructing a dynamic weight evaluation model for the safety risk of the navigation environment based on the weight fusion of subjective and objective impact factors. The waters under the jurisdiction of Sanya, China were selected for the study, and the navigation risk of the waters in the jurisdiction was calculated by using the dynamic weight evaluation model based on navigation risk. The calculation results are highly consistent with the results based on the statistics of historical accidents and the analysis of the characteristics of the navigation environment in the jurisdiction. The navigation risk in this water area is the greatest from May to September every year. The dynamic weight evaluation model can not only overcome the subjective evaluation distortion in the traditional risk evaluation theory of navigation environment in practical applications, but can also provide a scientific theoretical basis for the dynamic evaluation and early warning of the risk of ship navigation environments through continuous sample learning.

Clinical Reference Strategy for the Selection of Treatment Materials for Maxillofacial Bone Transplantation: A Systematic Review and Network Meta-Analysis - Shuxin Zhang; Xinyi Zhang; Yanli Li; Xuran Mao; Rui Liu; Yanxin Qi; Eui-Seok Lee; Heng Bo Jiang (Tissue Engineering and Regenerative Medicine, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Genetically encoded redox biosensor system for H2O2 measurement in four subcellular compartments in acute myeloid leukemia (AML) cells - Mengmeng Cui; Ghulam Abbas; Dianbing Wang; Qian Liu; Rui Gong; Min Li; Xian-En Zhang (Science China Life Sciences, 2022)

Characterization of Joint Roughness Heterogeneity and Its Application in Representative Sample Investigations - Shi-Gui Du; Hang Lin; Rui Yong; Guang-Jian Liu (Rock Mechanics and Rock Engineering, 2022)
Rock joint surface roughness is usually characterized by heterogeneity, but the determination of a required number of samples for achieving a reasonable heterogeneity assessment remains a challenge. In this paper, a novel method, the global search method, was proposed to investigate the heterogeneity of rock joint roughness. In this method, the roughness heterogeneity was characterized based on a statistical analysis of the roughness of all samples extracted from different locations of a given rock joint. Analyses of the effective sample number were conducted, which showed that sampling bias was caused by an inadequate number of samples. To overcome this drawback, a large natural slate joint sample (1000 mm × 1000 mm in size) was digitized in a laboratory using a high-accuracy laser scanner. The roughness heterogeneities of both two-dimensional (2D) profiles and three-dimensional (3D) surface topographies were systematically investigated. The results show that the expected value obtained from conventional methods failed to accurately represent the overall roughness. The relative errors between the population parameter and the expected value varied not only from sample to sample but also with the scale. The roughness heterogeneity characteristics of joint samples of various sizes can be obtained using the global search method. This new method could facilitate the determination of the most representative samples and their positions.

Bionic study of the cushioning and energy-saving joints of leg of the walking robot - Rui Zhang; Wenchao Dong; Lujiang Liu; Xuemei Ju; Hao Pang; Qingqiu Cao; Lige Wen (Rendiconti Lincei. Scienze Fisiche e Naturali, 2022)

Establishment and optimization of PEG-mediated protoplast transformation in the microalga Haematococcus pluvialis - Chunli Guo; Muhammad Anwar; Rui Mei; Xinyi Li; Di Zhao; Yanan Jiang; Jieyi Zhuang; Chen Liu; Chaogang Wang; Zhangli Hu (Journal of Applied Phycology, 2022)
Genetic manipulation of Haematococcus pluvialis is difficult because of the lack of a stable and convenient transformation system. The pH124-EGFP-Ble vector containing ble as a selective gene and EGFP as a reporter gene was constructed and employed for effective transformation. H. pluvialis protoplasts were obtained by treating with cellulase and macerozeme. Then polyethylene glycol-mediated transformation was established by incubating the protoplast with the vector. To improve the transformation efficiency of H. pluvialis protoplasts, the transformation system was optimized in consideration of different influencing factors, including zeomycin concentration, growth stage, amount of transformed vector, linearization of the vector, and duration of low-intensity illumination. The integration and expression of ble and EGFP was confirmed in the transformants. Moreover, the optimal combination for protoplast transformation of H. pluvialis was determined to be 5 µg of the linearized vector used to transform cells in the log growth phase, and then the transformed protoplasts allowed to recover under low-intensity illumination for 6 h. This study represents and describes the successful development of an H. pluvialis transformation protocol using protoplasts, which will enable convenient genetic manipulation of this important algal species.

C2CD4A/B variants in the predisposition of lung cancer in the Chinese Han population - Feifei Han; Lu Qian; Yi Zhang; Ping Liu; Rui Li; Mingwei Chen (Functional & Integrative Genomics, 2022)

Plant contribution to the remediation of PAH-contaminated soil of Dagang Oilfield by Fire Phoenix - Xiaomei Wang; Jianping Sun; Rui Liu; Tingyu Zheng; Yingnan Tang (Environmental Science and Pollution Research, 2022)

Rural-urban differences in associations between air pollution and cardiovascular hospital admissions in Guangxi, southwest China - Guangli Zhang; Xiaoxiao Liu; Shiyan Zhai; Genxin Song; Hongquan Song; Lizhong Liang; Yunfeng Kong; Rui Ma; Xinxin He (Environmental Science and Pollution Research, 2022)

Geochronology, Geochemistry and Geological Significance of Volcanic Rocks of the Bangba District, Western Segment of the Central Lhasa Subterrane - Yan Cao; Zhiqiang Kang; Feng Yang; Tong Zhou; Dongmei Liu; Rui Wang (Journal of Earth Science, 2022)

Combining gradual and abrupt analysis to detect variation of vegetation greenness on the loess areas of China - Panxing He; Zongjiu Sun; Dongxiang Xu; Huixia Liu; Rui Yao; Jun Ma (Frontiers of Earth Science, 2022)

Roseococcus pinisoli sp. nov., lacking pufL and pufM bacteriochlorophyll a: synthesizing genes - Lei Shen; Miao-miao An; Rui-na Liang; Peng-xiao Liu; Xiang-wei He; Guo-zhu Zhao (Archives of Microbiology, 2022)

Logging evaluation of shale oil “sweet spot” in Da’anzhai member, Longgang area, Sichuan Basin - Zonghui Lin; Jungang Lu; Rui Zhang; Shaoming Zhang; Longxiang Tang; Zhanghao Liu; Yaoting Li (Arabian Journal of Geosciences, 2022)

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Hippocampal Activated Microglia May Contribute to Blood–Brain Barrier Impairment and Cognitive Dysfunction in Post-Traumatic Stress Disorder-Like Rats - Kun Ni; Jixiang Zhu; Xuan Xu; Yue Liu; Shuai Yang; Yulin Huang; Rui Xu; Li Jiang; Juan Zhang; Wei Zhang; Zhengliang Ma (Journal of Molecular Neuroscience, 2022)

Experimental study on the pore and solid structures of municipal solid waste under compression based on computed tomography (CT) scans - Han Ke; Ying Liu; Meng Meng; Jie Hu; Shi Yu Zhao; Rui Qin; Xiao Wen Wu (Environmental Science and Pollution Research, 2022)

Geochronological, geochemical, and P–T path constraints on the late Paleoproterozoic continent–continent collision orogeny in the Quruqtagh Block, Tarim Craton - Tao Cui; Shan-Shan Li; Rui-Qing Guo; Germain Bishikwabo; Xiang-Kuan Gong; Gui-Ping Liu; Yu Guo (Arabian Journal of Geosciences, 2022)

A novel microRNA regulates cooperation between symbiont and a laterally acquired gene in the regulation of pantothenate biosynthesis within Bemisia tabaci whiteflies - Xiang Sun; Bing‐Qi Liu; Chu‐Qiao Li; Zhan‐Bo Chen; Xiao‐Rui Xu; Jun‐Bo Luan (Molecular Ecology, 2022)
Horizontally transferred genes (HTGs) play a key role in animal symbiosis, and some horizontally transferred genes or proteins are highly expressed in specialized host cells (bacteriocytes). However, it is not clear how HTGs are regulated, but microRNAs (miRNAs) are prime candidates given their previously demonstrated roles in symbiosis and impacts on the expression of host genes. A horizontally acquired PanBC that is highly expressed in whitefly bacteriocytes can cooperate with an obligate symbiont Portiera for pantothenate production, facilitating whitefly performance and Portiera titre. Here, we found that a whitefly miRNA, novel‐m0780‐5p, was up‐regulated and its target panBC was down‐regulated in Portiera ‐eliminated whiteflies. This miRNA was located in the cytoplasmic region of whitefly bacteriocytes. Injection of novel‐m0780‐5p agomir reduced the expression of PanBC in whitefly bacteriocytes, while injection of novel‐m0780‐5p antagomir enhanced PanBC expression. Agomir injection also reduced the pantothenate level, Portiera titre and whitefly performance. Supplementation with pantothenate restored Portiera titre and the fitness of agomir‐injected whiteflies. Thus, we demonstrate that a whitefly miRNA regulates panBC ‐mediated host–symbiont collaboration required for pantothenate synthesis, benefiting the whitefly– Portiera symbiosis. Both panBC and novel‐m0780‐5p are present in the genomes of six Bemisia tabaci species. The expression of a novel miRNA in multiple B . tabaci species suggests that the miRNA evolved after panBC acquisition, and allowed this gene to be more tightly regulated. Our discovery provides the first account of a HTG being regulated by a miRNA from the host genome, and suggests key roles for interactions between miRNAs and HTGs in the functioning of symbiosis.

Evolutionary and ecological patterns of scatter‐ and larder‐hoarding behaviours in rodents - Yongjun Zhang; Fei Yu; Xianfeng Yi; Weiwei Zhou; Rui Liu; Marcel Holyoak; Lin Cao; Mingming Zhang; Jiani Chen; Zhibin Zhang; Chuan Yan (Ecology Letters, 2022)
Scatter‐ and larder hoarding are the primary strategies of food‐hoarding animals and have important implications for plant‐animal interactions and plant recruitment. However, their origins and influencing factors have not been fully investigated across a wide range of taxa. Our systematic literature search amassed data for 183 seed‐hoarding rodent species worldwide and tested relationships of seed‐hoarding behaviours with phylogenetic signal, functional traits and environmental factors. We found that the evolution of hoarding strategies was not random in phylogeny, and scatter hoarding originated independently multiple times from larder hoarding. Rodents with higher encephalisation quotient (relative brain size), omnivorous diet (related to dependence on seeds) and inhabiting lower latitudes were disproportionately likely to scatter hoard. Despite body mass’s potential relationship with competition through food defence, it was associated with food‐hoarding strategy only in a few families. Our results show the need to study the community and ecological context of food‐hoarding behaviours.

Flower colour and essential oil compositions, antibacterial activities in Lagerstroemia indica L. - Qiang Wei; Rui-jie Liu (Natural Product Research, 2022)

Cultivation and Functional Characterization of a Deep-Sea Lentisphaerae Representative Reveals Its Unique Physiology and Ecology - Tianhang Zhang; Rikuan Zheng; Rui Liu; Ronggui Li; Chaomin Sun (Frontiers in Marine Science, 2022)
As a member of Planctomycetes – Verrucomicrobia – Chlamydia (PVC) superphylum, the phylum Lentisphaerae is broadly distributed in various environments. Lentisphaerae members have been recognized as being typically difficult to isolate in pure culture—only five strains belonging to this phylum were cultured up to now—and therefore their major physiology and ecology are largely unknown. Here, using a polysaccharide degradation-driven strategy, we successfully cultured a representative of Lentisphaerae bacteria ( Candidatus Coldseepensis marina zth2) from the deep-sea cold seep. Based on physiological and phylogenetic analyses, strain zth2 is identified as a type strain of a novel family. Notably, strain zth2 divides by a budding manner and a unique feature seen in ultrathin-section electron microscopic observation is the occurrence of narrow protrusions, namely, both cell wall and cytoplasm on the surface of strain zth2. Through growth assays and transcriptomic analyses, strain zth2 was verified to efficiently utilize polysaccharides, phosphate, and iron for growth. Strikingly, the utilization of polysaccharide, phosphate, and iron is correlative and jointly contributes to carbon, phosphorus, and iron metabolisms and thereby facilitating the production of energy. By mimicking the ocean environment and using operational taxonomic units (OTUs) analysis, we demonstrated that strain zth2 significantly enrich the microbial diversity by metabolizing polysaccharides or other substances. Overall, we propose that Lentisphaerae members are potential contributors to the cycling of nutrient, carbon, phosphorus, and other elements in the deep biosphere.

Research progress on antimicrobial materials for food packaging - Saeed Ahmed; Dur E. Sameen; Rui Lu; Rui Li; Jianwu Dai; Wen Qin; Yaowen Liu (Critical Reviews in Food Science and Nutrition, 2022)

Two new dammarane-type triterpenoids from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hui-Rui Gao; Hong-Juan Song; Dan-Da Ma; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Xiao-Li Wang; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Rare soil species impact the rhizosphere bacterial communities and cadmium uptake by Lolium multiflorum Lam. - Chenxin Gao; Yan Zhu; Xian Xiao; Rui Liu; Xuesong Zhu; Yuan Zhao (Plant and Soil, 2022)

Glyphosate-induced GhAG2 is involved in resistance to salt stress in cotton - Wancong Yu; Zhaohui Xue; Xianzheng Zhao; Rui Zhang; Jiping Liu; Sandui Guo (Plant Cell Reports, 2022)

Effects of different energy diets on DNA methylation and mRNA expression in follicle stimulating hormone receptor gene promoter region of Duolang sheep during estrus - Bo Liu; Hongjian Li; Weikun Tao; Fei Huang; Xue Rui; Jie Wang; Peng Niu; Di Fang; Qinghua Gao (Molecular Biology Reports, 2022)

Interaction between organic matter and tetracycline in river sediments in cold regions - Changyong Wu; Rui Tang; Huiqi Li; Xiang Liu; Liya Fu; Yin Yu; Chunli Wan (Environmental Science and Pollution Research, 2022)

Occurrence of titanium dioxide nanoparticle in Taihu Lake (China) and its removal at a full-scale drinking water treatment plant - Zhiyuan Liu; Min Rui; Shuili Yu (Environmental Science and Pollution Research, 2022)

Correction to: Desiccation cracking in clay‑bottom ash mixtures: insights from crack image analysis and digital image correlation - Rui Liu; Mark Vail; Behrad Koohbor; Cheng Zhu; Chao‑Sheng Tang; Hao Xu; Xiang‑Chao Shi (Bulletin of Engineering Geology and the Environment, 2022)

Desiccation cracking in clay-bottom ash mixtures: insights from crack image analysis and digital image correlation - Rui Liu; Mark Vail; Behrad Koohbor; Cheng Zhu; Chao-Sheng Tang; Hao Xu; Xiang-Chao Shi (Bulletin of Engineering Geology and the Environment, 2022)

Focal white matter microstructural alteration after anthracycline-based systemic treatment in long-term breast cancer survivors: a structural magnetic resonance imaging study - Huawen Zhang; Peng Li; Tonghui Liu; Xueyuan Wang; Wei Feng; Rui Chen; Hengyang Wei; Guoqiang Li; Long Ning; Ming Zhang; Yuchen Zhang (Brain Imaging and Behavior, 2022)

Face failure mechanism of shield tunnel in sandy ground with different low moisture contents - Zhongrong Wang; Wantao Ding; Xinghang Huang; Rui Chen; Keqi Liu (Arabian Journal of Geosciences, 2022)

Timing constraints on alkaline magmatic activity and implications for lithospheric thinning beneath the North China Craton: evidence from zircon geochronology of syenite from the Huyanshan complex in the Lyuliangshan uplift belt, Shanxi Province - Yanhai Liu; Guangui Zou; Rui Zhou; Dongna Liu (Arabian Journal of Geosciences, 2022)

Petrogenesis and tectonic setting of the early-middle triassic subduction-related granite in the eastern segment of East Kunlun: evidences from petrology, geochemistry, and zircon U-Pb-Hf isotopes - Zuo-Chen Li; Xian-Zhi Pei; Paul D. Bons; Rui-Bao Li; Lei Pei; Guo-Chao Chen; You-Xin Chen; Cheng-Jun Liu; Meng Wang; Shao-Wei Zhao; Xiao-Bing Li; Feng Gao (International Geology Review, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

A switch-on molecular biosensor for detection of caspase-3 and imaging of apoptosis of cells - Rui Gong; Dianbing Wang; Ghulam Abbas; Shimin Li; Qian Liu; Mengmeng Cui; Xian-En Zhang (Science China Life Sciences, 2022)

Early changes to the extracellular space in the hippocampus under simulated microgravity conditions - Yajuan Gao; Hongbin Han; Jichen Du; Qingyuan He; Yanxing Jia; Junhao Yan; Hui Dai; Bin Cui; Jing Yang; Xunbin Wei; Liu Yang; Rui Wang; et al. (Science China Life Sciences, 2022)

Glacier lanternfish (Benthosema glaciale) first found on the continental slope of the Pacific Arctic - Ran Zhang; Yuan Li; Qiaohong Liu; Puqing Song; Hai Li; Rui Wang; Shaoxiong Ding; Longshan Lin (Polar Biology, 2022)

Identification and Expression Analysis of the SBP-box Gene Family Related to Abiotic Stress in Tea Plant (Camellia sinensis (L.) O. Kuntze) - Rui-Min Teng; Yong-Xin Wang; Hui Li; Hao Liu; Yu Wang; Jing Zhuang (Plant Molecular Biology Reporter, 2022)

Regulation of Social Memory by Lateral Entorhinal Cortical Projection to Dorsal Hippocampal CA2 - Rui Dang; Yu Zhou; Yue Zhang; Die Liu; Miao Wu; An Liu; Zhengping Jia; Wei Xie (Neuroscience Bulletin, 2022)

QTL mapping and candidate gene prediction for fiber yield and quality traits in a high-generation cotton chromosome substitution line with Gossypium barbadense segments - Quanwei Lu; Pengtao Li; Rui Yang; Xianghui Xiao; Ziyin Li; Qiuyu Wu; Juwu Gong; Qun Ge; Aiying Liu; Shengli Du; Jundi Wang; Yuzhen Shi; et al. (Molecular Genetics and Genomics, 2022)

Pseudonocardia humida sp. nov., an Actinomycete Isolated from Mangrove Soil Showing Distinct Distribution Pattern of Biosynthetic Gene Clusters - Zhen-Yu Zan; Xian-Feng Ge; Rui-Rui Huang; Wen-Zheng Liu (Current Microbiology, 2022)

Anaerobic digestion characteristics and key microorganisms associated with low-temperature rapeseed cake and sheep manure fermentation - Li Liu; Rongbo Xiong; Yi Li; Laisheng Chen; Rui Han (Archives of Microbiology, 2022)

Dysfunction of FadA‐cAMP signalling decreases Aspergillus flavus resistance to antimicrobial natural preservative Perillaldehyde and AFB1 biosynthesis - Kunlong Yang; Qingru Geng; Yue Luo; Rui Xie; Tongzheng Sun; Zhen Wang; Ling Qin; Wei Zhao; Man Liu; Yongxin Li; Jun Tian (Environmental Microbiology, 2022)
Summary Aspergillus flavus is an opportunistic fungal pathogen that colonizes agriculture crops with aflatoxin contamination. We found that Perillaldehyde (PAE) effectively inhibited A . flavus viability and aflatoxin production by inducing excess reactive oxygen species (ROS). Transcriptome analysis indicated that the Gα protein FadA was significantly induced by PAE. Functional characterization of FadA showed it is important for asexual development and aflatoxin biosynthesis by regulation of cAMP‐PKA signalling. The Δ fadA mutant was more sensitive to PAE, while Δ pdeL and Δ pdeH mutants can tolerate excess PAE compared to wild‐type A . flavus . Further RNA‐sequence analysis showed that fadA was important for expression of genes involved in oxidation–reduction and cellular metabolism. The flow cytometry and fluorescence microscopy demonstrated that Δ fadA accumulated more concentration of ROS in cells, and the transcriptome data indicated that genes involved in ROS scavenging were downregulated in Δ fadA mutant. We further found that FadA participated in regulating response to extracellular environmental stresses by increasing phosphorylation levels of MAPK Kinase Slt2 and Hog1. Overall, our results indicated that FadA signalling engages in mycotoxin production and A . flavus resistance to antimicrobial PAE, which provide valuable information for controlling this fungus and AF biosynthesis in pre‐ and postharvest of agricultural crops.

Establishing a Risk Assessment Framework for Marine Assets and Assessing Typhoon Lekima Storm Surge for the Laizhou Bay Coastal Area of the Bohai Sea, China - Jian Li; Dongxue Mo; Rui Li; Yijun Hou; Qingrong Liu (Journal of Marine Science and Engineering, 2022)
Effective risk assessment can reduce the economic losses and physical damage caused by marine dynamic processes, such as storm surges. Most risk assessments of marine disasters are based on regional parameters and discrete hazard grades. Targeted, multilevel, and multiangle risk assessments are urgently needed. This study focuses on specific types of affected infrastructure. We established a sensitivity matrix by considering the effects of different disaster causal factors on different types of affected infrastructure. Through this matrix, hazards, vulnerability, and emergency response and recovery capability were effectively combined in a risk assessment framework. We completed the risk calculation for multiple concurrent effects of disasters in areas with superimposed key infrastructure using complementary risk superposition. The hazard grade, vulnerability grade, and coefficient of emergency response and recovery capability were established based on the means of return period, characteristics of disaster distribution, types of affected infrastructure and disaster relief distance, and were continuous by solving functions, normal cumulative distributions, and analytic functions. On the basis of reasonable MIKE21 numerical simulation and abstract spatial distribution of vulnerable assets, we tested the rationality of the assessment system in the Lekima typhoon storm surge process. The results showed that the assessment system accurately reflected the risk of damage to the important infrastructure in terms of spatial distribution. Therefore, this risk assessment framework was suitable for the assessment of a marine dynamic disaster process in the lower Laizhou Bay coastal area of the Bohai Sea, China. Moreover, it provided a reference for disaster prevention and reduction, guided the way for decision making, and effectively reduced disaster losses.

Cytotoxic α-pyrone derivatives from Cryptocarya yunnanensis - Qian He; Yue Fan; Yu Liu; Yun-Xia You; Li Rao; Yu Su; You-Kai Xu; Bin Lin; Chuan-Rui Zhang (Natural Product Research, 2022)

Microglial SIRPα Deletion Facilitates Synapse Loss in Preclinical Models of Neurodegeneration - Chongyun Wu; Luodan Yang; Hannah Youngblood; Timon Cheng-Yi Liu; Rui Duan (Neuroscience Bulletin, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Nitrogen and carbon addition changed nitrous oxide emissions from soil aggregates in straw-incorporated soil - Junhui Yin; Rui Liu; Wenchao Cao; Kun Zhu; Owen Fenton; Jingheng Guo; Qing Chen (Journal of Soils and Sediments, 2022)

MiR-582-3p participates in the regulation of biological behaviors of A549 cells by ambient PM2.5 exposure - Mei Yang; Liangliang Ju; Changlian Li; Han Cheng; Na Li; Qi Zhang; Shu Sun; Liu Ding; Xinmiao Sui; Chao Zhang; Mingwei Yang; Jiyu Cao; et al. (Environmental Science and Pollution Research, 2022)

Janibacter endophyticus sp. nov., an Endophytic Actinobacterium Isolated from the Root of Paris polyphylla Smith var. Yunnanensis - Zhen Zhang; En-Min Zhou; Cong-Jian Li; Xing-Wang Jiang; Rui-Feng Mao; Jing-Ran Liu; Xiao-Yang Zhi; Ling-Ling Yang (Current Microbiology, 2022)

Interaction of influenza A virus NS1 and cytoskeleton scaffolding protein α-actinin 4 - Yingyue Zeng; Rui Wang; Fengchao Wang; Man Zhang; Li Zhang; Chunyu Zhu; Jian Zhao; Hongsheng Liu (Virus Genes, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

The responses of detoxification enzyme and gene expression in western flower thrips, Frankliniella occidentalis, to new challenging hosts - Wen-Bo Yue; Jun-Rui Zhi; Li Liu; Xiao-Lin Hou; Mao Ye (Arthropod-Plant Interactions, 2022)

Neobacillus paridis sp. nov., an endophyte of Paris polyphylla Smith var. yunnanensis - Peng-Chao Zhan; Cong-Jian Li; Zhen Zhang; Rui-Feng Mao; Jing-Ran Liu; Xing-Wang Jiang; Xiao-Yang Zhi; Ling-Ling Yang (Archives of Microbiology, 2022)

RNA interference-mediated knockdown of tripartite motif containing 44 suppresses cervical cancer growth in vitro and in vivo - Rui Liu; Yanan Ma; Wenli Gu; Canxu Song; Lina Zhou; Huanran Meng; Yuan Zhang; Caihong Yang (Molecular & Cellular Toxicology, 2022)

Aflatoxin B 1 and sterigmatocystin: method development and occurrence in tea - Yarong Zhao; Rui Zeng; Qiongshan Wang; Peirong Chen; Xiangxiang Liu; Xu Wang (Food Additives & Contaminants Part B-Surveillance, 2022)

Enhanced stripe rust resistance obtained by combining Yr30 with a widely dispersed, consistent QTL on chromosome arm 4BL - Shengjie Liu; Xiaoting Wang; Yayun Zhang; Yangang Jin; Zhonghua Xia; Mingjie Xiang; Shuo Huang; Linyi Qiao; Weijun Zheng; Qingdong Zeng; Qilin Wang; Rui Yu; et al. (Theoretical and Applied Genetics, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Organic-rich formation and hydrocarbon enrichment of lacustrine shale strata: A case study of Chang 7 Member - Quanyou Liu; Peng Li; Zhijun Jin; Yuewu Sun; Guang Hu; Dongya Zhu; Zhenkai Huang; Xinping Liang; Rui Zhang; Jiayi Liu (Science China Earth Sciences, 2022)

Molecular cloning and functional characterization of two squalene synthase genes in Atractylodes lancea - Junxian Wu; Rui Xu; Jimei Lu; Weiwei Liu; Hanwen Yu; Mengli Liu; Jing Li; Minzhen Yin; Huasheng Peng; Liangping Zha (Planta, 2022)

Roots and microbiome jointly drive the distributions of 17 phytohormones in the plant soil continuum in a phytohormone‐specific manner - Yuqiu Lu; Enzhao Wang; Zhiyu Tang; Junpeng Rui; Yanling Li; Zhixi Tang; Weiling Dong; Xiongduo Liu; Timothy S. George; Alin Song; Fenliang Fan (Plant and Soil, 2022)

Correction to: Isorhamnetin protects against cardiac hypertrophy through blocking PI3K–AKT pathway - Lu Gao; Rui Yao; Yuzhou Liu; Zheng Wang; Zhen Huang; Binbin Du; Dianhong Zhang; Leiming Wu; Lili Xiao; Yanzhou Zhang (Molecular and Cellular Biochemistry, 2022)

Peripheral Administration of an Opioid Peptide Analog Ameliorates Morphine-Produced Hyperalgesia in a Spared Nerve Injury Model - Yuan Wang; Meng-tao Ma; Jing Wang; Chao-zhen-yi Han; Kai Li; Qiao-min Ru; Na Li; Xin Liu; Rui Wang (International Journal of Peptide Research and Therapeutics, 2022)

Air pollution increased risk of reproductive system diseases: a 5-year outcome analysis of different pollutants in different seasons, ages, and genders - Ya Li; Juan Du; Shanshan Lin; Huihui He; Rui Jia; Weihong Liu (Environmental Science and Pollution Research, 2022)

Identification and Characterization of a Novel Soluble Pyridine Nucleotide Transhydrogenase from Streptomyces avermitilis - Zhengyu Cao; Jie Liu; Rui Meng; Peng Wang; Guoping Zhu (Current Microbiology, 2022)

The specialized mitotic behavior of human embryonic stem cells - Rui Lyu; Xuemei Wu; Nan Ma; Difei Wang; Shuang Sun; Youguang Luo; Jun Zhou; Xinyi Lu; Min Liu; Dengwen Li (Cell and Tissue Research, 2022)

Kangiella shandongensis sp. nov., a novel species isolated from saltern in Yantai, China - Li-Yang Peng; Rui Yin; Shu-Kun Gao; Hui-Ning Jiang; Xiao-Xiao Liu; Yu Ma; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2022)

Linking net interaction effects with network topologies in food webs - Chuan Yan; Yongjun Zhang; Rui Liu (Global Ecology and Biogeography, 2022)
Aim The difficulty in predicting responses to press perturbation is largely due to the tangled nature of indirect interactions in natural ecological networks. Although previous theories have paved the way for evaluating net interaction effects by incorporating direct and indirect effects related to press perturbation, there are still critical knowledge gaps regarding the relationships between net interaction effects and network topologies because of lack of comparable interaction strengths across ecosystems. Location Global. Time period 1984–2020. Major taxa studied Aquatic organisms. Methods We compiled a global dataset of food webs with a consistent modelling method to estimate direct interaction strength. We revealed the general patterns of net interaction effects and their associations with network topologies by applying matrix theory and network analysis. Results In the examined food webs, the net (absolute) interaction strengths followed a right‐skewed pattern (many weak and few strong net strengths) and were significantly associated with various network‐ and species‐level topological structures. Indirect effects led to the emergence of net mutualism and competition effects rather than simply net predator–prey interaction effects, and might play an important role in changing signs from direct to net interaction effects in species‐rich and highly connected food webs and for species with a large number of interaction partners. Main conclusions Our results highlight the ecological significance and necessity of linking net interaction effects with network topologies, which can help target ecosystems and species that are more vulnerable to sustained perturbation in the application of conservation and biodiversity management.